Features of the course of pregnancy and child birth in a patient with liver transplantation from a living donor - Gulnar Murzabekova; Karligash Togyzbaeva; Togzhan Payayeva; Aigerym Nurmanova; Arlan Rakhatayev (National Scientific Medical Center, 2017)
This paper describes a clinical case of pregnancy and delivery in patients with liver transplantation from a living donor . This case demonstrates the possibility of pregnancy in women who have undergone transplant rejection crisis and successful delivery. Liver transplantation is not anindication for surgical delivery.